Enhancer, epigenetics, and human disease. (February 2016) - Luo, Zhuojuan; Lin, Chengqi
Abstract : Enhancers encode a huge body of information to determine the precise tissue specific gene expression pattern during normal development. Nowadays, enhancers are also considered as key players in directing disease transcriptional program during pathogenesis. New genomic technologies allow the identification, functional characterization and manipulation of enhancers. The advances in the transcriptional enhancer field hold great promise in linking developmental or disease phenotypes to genetic variants and promoting precision medicine.